Modelling the Sensitivity of the KM3NeT/ARCA and KM3NeT/ORCA to Neutrinos from Quiescent Blazars - Nkosi, Bhuti Linda (University of the Witwatersrand, Johannesburg, 2023)
Blazar jet emission has been modelled using two families of models, leptonic and hadronic, to explain the double-peaked SED. In hadronic models, the higher energy peak is explained by proton interactions with the jet material and external fields. Lepto-hadronic models are a type of blazar emission model that accounts for both leptonic and hadronic processes in the jet. In these models, the low-energy bump of the spectral energy distribution SED is produced by synchrotron radiation from primary electrons, while the high-energy bump is produced by a combination of radiation from protons and secondary particles. Lepto-hadronic models can explain the variability and spectral features of blazars in different states, such as flaring or quiescent. In this project, we used a one-zone lepto-hadronic model to simulate the blazar jet and calculate the neutrino emission and detection prospects with KM3NeT.
A Dissertation submitted in fulfillment of the requirements for the degree of Master of Science (Physics), to the Faculty of Science, School of Physics, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Blazars; Neutrinos; KM3NeT; Hadronic; UCTD; SDG-9: Industry, innovation and infrastructure